Communication of trainers as one of the means for customer retention in fitness clubs - Bartha , Éva; Perényi , Szilvia (Applied Studies in Agribusiness and Commerce, 2015)
Acquiring the adequate communication style is a vital element in trainers’ profession. This research aims to reveal the effects generated via the communicative style by trainers of fitness club customers. It also intends to explore whether communication style has any relation to the regularity of class attendance as well as to the length of training periods which is conceptualised in this paper as trainers’ economic efficiency. Data collection was carried out by structured interviews in a country-side large sport centre. Trainers with at least three training sessions per week (N=20) and their groups (N=160) were interviewed using Rudas (1994) communication style survey and additional selfdeveloped interview protocols. The results revealed that the examined trainers were distributed in all four communications styles, but showing dominance in aggressive and passive styles. The classes of trainers with aggressive and assertive communication style were those that showed the highest and maintained attendance rates. It seems, that classes held by trainers who communicate in a deliberate way and convey positive messages are attended more and in a sustained way. Accordingly, their precisely set targets and explanation of training sessions content correlated with repeated attendance and customer retention. It seems that groups with extended scope of communication are characterised by stronger group cohesion where social relationships could develop easier, which have relations to perseverance and commitment. Therefore development of trainers’ communication skills may be considered as an effective tool for fitness clubs for customer retention. JEL code: Z20